Desperado [videorecording (DVD)] - Rodriguez, Robert, 1968-; Borden, Bill (Film producer); Banderas, Antonio; Almeida, Joaquim de, 1957-; Hayek, Salma, 1966-; Navarro, Guillermo; Montiel, Cecilia (Columbia TriStar Home Entertainment, 2003)
A mysterious guitar player seeks vengeance against the men who murdered his girlfriend --